Benefits of integration of cereals and forage legumes with and without crossbred cows in mixed farms - an ex ante analysis for highland Ethiopia - Kassie, M.; Jabbar, M.A.; Kassa, B.; Mohamed-Saleem, M.A. (Informa UK Limited, 1999)
Poverty, low crop and animal productivity and large scale resource degradation are major problems in the agriculture sector in the East African highlands. Among others, integration of forage legumes in cereal based cropping systems has been proposed as a promising strategy to improve the sustainability of smallholder farming systems through increased crop and livestock productivity and better soil management. Using experimental data from Ethiopia and elsewhere in the region, linear programming models have been used to determine the economic impacts of cereal-forage legume inter-cropping with and without crossbred cows for a typical highland mixed farm. An important feature of the model was that the benefits of inter-cropping in terms of nitrogen fixation and the better nutrition of animals were accounted for. Model results demonstrate that the introduction of forage legumes with cereals changes cropping pattern significantly, but does not significantly change the use pattern of principal farm resources, labor and ox power. Introduction of cereal-forage legume inter-cropping significantly increases gross margin and cash income, and the introduction of crossbred cows enhances these returns even further. Inter-cropping also significantly increases the share of livestock in farm and cash income when crossbred cows are included. Sensitivity analyses show that the improved technologies remain more profitable than current practices eve when there is a substantial decrease in price of outputs. The results indicate that the improved production technologies should be widely tested under actual farm conditions under farmer management through on-farm research and extension. Benefits of inter-cropping in terms of weed control and control of soil erosion should be quantified in future research.